Ethical considerations in research. Focus on vulnerable groups - Shaké Ketefian (Universidad de Antioquia, 2015)
The purpose of this paper was to describe the need to protect the rights of human subjects participating in nursing research, and procedures for doing so. The path taken to the task at hand was to approach the topic by discussing the philosophical underpinnings of human subject protection and describing the approach for doing this in all cases where humans are used as research subjects. These underpinnings include specific ethical principles of respect for persons, beneficence, and justice, and the procedures used in the U.S. for protecting the rights of human subjects. Once the process was clarified, the considerations necessary to protect the special groups referred to as ''vulnerable'' are discussed. Given the author's access to U.S. documents and the fact that U.S. government agencies took early steps to formalize rules and regulations for the protection of human subjects, vulnerable or otherwise, the experience of the United States was selected for presentation. It is recognized that there are now relevant international documents that are exceedingly helpful, and also, that various countries may have their own guidelines for investigators to follow. In such cases researchers can engage in comparative analysis between their own guidance and the processes described here, and decide their path accordingly.